MATHEMATICAL REPRESENTATION BASED ON PERSONALITY TYPES - Sitti Zuhaerah Thalhah; Thamrin Tayeb; Sumardin Raupu; Dwi Risky Arifanti (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aims at describing the mathematical representation of students with Sanguine, Choleric, Melancholic and Phlegmatic personality types in solving linear program problems. The instrument used was a personality test adapted from the Personality Plus book by Florence Litteur. The data were collected by applying linear programming problems to the main subjects that represent each personality type. The results of Sanguine and Melancholy students only represented three indicators, the problem were not represented in the form of diagrams, graphs, tables or drawings, while, the Choleric and phlegmatic students represented problems in four indicators. Another finding, the sanguine students answered all the questions correctly but did not make the conclusions. The Choleric and melancholy students were less focus on the calculation process so there were some answers incorrectly, while all phlegmatic students answered incorrectly.Abstrak:Penelitian ini bertujuan untuk mendeskripsikan representasi matematis mahasiswa bertipe kepribadian sanguinis, korelis, melankolis dan phlegmatis dalam menyelesaian masalah program linier. Jenis penelitian ini adalah penelitian kualitatif. Adapun instrumen yang digunakan adalah tes kepribadian yang diduplikasi dari buku Personality Plus karya Florence Litteur, lembar tes kemampuan representasi matematis dan wawancara. Data dikumpulkan dengan memberikan masalah program linier kepada subjek utama yang mewakili masing-masing tipe kepribadian, kemudian dianalisis berdasarkan indikator representasi matematis. Hasil analisis yang diperoleh, yaitu mahasiswa sanguinis dan melankolis hanya merepresentasikan tiga indikator, masalah tidak direpresentasikan dalam bentuk diagram, grafik, table atau gambar, sedangkan mahasiswa korelis dan phlegmatis merepresentasikan masalah dalam empat indikator. Temuan lain, mahasiswa sanguinis menjawab semua soal dengan benar namun tidak melakukan penarikan kesimpulan. Mahasiswa korelis dan melankolis kurang teliti dalam melakukan proses perhitungan sehingga ada soal yang dijawab salah, sedangkan mahasiswa phlegmatis semua soal dijawab salah.